Processing of duplex stainless steel by WEDM - Pramanik, Alokesh; Basak, A.; Dixit, A.; Chattopadhyaya, S. (Springer, 2018)
This study investigates the manufacturing process of 2205 duplex stainless steel by wire electrical discharge machining where the effects of pulse-on time (PONT), wire tension and pulse-off time (POFT) on surface finish, kerf width, and material removal rate (MRR). It was found that the kerf width was unchanged with the change of PONT at long pulse-of time and higher wire tension. However, it decreased initially and then increased due to the rise of PONT at low values of wire tension and POFT. Low wire tension and PONT, POFT and contributed towards widest kerf. Longer PONT increased MRR due to higher machining/processing speed. Lower wire tension and shorter POFT increased MRR more than that of higher wire tension and POFT. Craters and recast layer were on the machined surfaces at all machining conditions. Increased PONT raised surface roughness at the lower POFT and tension in the wire. The surface finish at high wire tension and longer PONT is always better than that at smaller PONT and lower tension in the wire. The microstructure underneath the recast layer remains unchanged and the failure of wire electrode occurred at higher wire tension, longer PONT and shorter POFT.